2017
DOI: 10.3928/01913913-20161019-01
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Outcomes of Stage III or Stage IV Retinoblastoma in 80 Asian Indian Patients

Abstract: Compliant multimodality treatment is beneficial in patients with IRSS stage III disease. IRSS stage IV retinoblastoma has poor prognosis despite treatment. [J Pediatr Ophthalmol Strabismus. 2017;54(3):177-184.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Munier, et al Progress in Retinal and Eye Research 73 (2019) 100764 up motivated by clinical features at presentation, presence of classic high-risk pathologic findings (Sastre et al, 2009), or possibly by the degree of anaplasia (Mendoza et al, 2015) after enucleation, or in symptomatic patients during/after conservative treatment. In most cases of metastatic disease at diagnosis, massive orbital extension occurs along with distant metastatic dissemination (Kaliki et al, 2017). The detection of minimally disseminated disease in bone marrow and cerebro-spinal fluid at diagnosis and follow-up can be now evaluated by means of quantitative polymerase chain reaction of cone-rod homeobox (CRX) transcription factor messenger RNA (Laurent et al, 2016).…”
Section: Diagnosis Of Metastatic Retinoblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Munier, et al Progress in Retinal and Eye Research 73 (2019) 100764 up motivated by clinical features at presentation, presence of classic high-risk pathologic findings (Sastre et al, 2009), or possibly by the degree of anaplasia (Mendoza et al, 2015) after enucleation, or in symptomatic patients during/after conservative treatment. In most cases of metastatic disease at diagnosis, massive orbital extension occurs along with distant metastatic dissemination (Kaliki et al, 2017). The detection of minimally disseminated disease in bone marrow and cerebro-spinal fluid at diagnosis and follow-up can be now evaluated by means of quantitative polymerase chain reaction of cone-rod homeobox (CRX) transcription factor messenger RNA (Laurent et al, 2016).…”
Section: Diagnosis Of Metastatic Retinoblastomamentioning
confidence: 99%
“…Although retinoblastoma is a chemosensitive tumor, metastatic disease is not curable with conventional treatment and is therefore considered to have a poor prognosis, especially in cases of CNS involvement (Kaliki et al, 2017;Pant et al, 2017). High dose chemotherapy, followed by autologous stem cell rescue with radiation to the sites of bulky disease, has been the only treatment reported to date to potentially cure these patients (Dunkel et al, 2010c;Palma et al, 2012), allowing remission in close to 70% of children in a series of 15 patients with metastatic retinoblastoma not involving the CNS (Dunkel et al, 2010c), whereas those with CNS involvement have only anecdotally benefitted from it (Dunkel et al, 2010a).…”
Section: Treatment Of Metastatic Retinoblastomamentioning
confidence: 99%
“…Shah et al reported 55.5% overall survival rate in children with Stage 3 and 4 disease at presentation [21]. Kaliki et al analyzed 80 patients with stage 3 or stage 4 disease at presentation and found that the survival rate were 71 and 0% in stage 3 and 4, respectively [23].…”
Section: Retinoblastoma In Indiamentioning
confidence: 99%
“…Stage 4 as judged from massive orbital tumour or visible nerve resection margin involvement signaling metastasis is incurable in this setting. This has been shown also in India even when advanced imaging and radiotherapy are available and justifies the decision for palliation alone in Stage 4 disease [20]. Second line chemotherapeutic protocols are available if the standard agents fail but as yet are of uncertain efficacy.…”
Section: Discussionmentioning
confidence: 96%